Carotenoprotein from Pacific white shrimp (Litopenaeus vannamei) shells extracted using trypsin from albacore tuna (Thunnus alalunga) spleen: Antioxidant activity and its potential in model systems. Issue 2 (22nd November 2017) - Poonsin, Tanchanok; Simpson, Benjamin K.; Benjakul, Soottawat; Visessanguan, Wonnop; Yoshida, Asami; Klomklao, Sappasith
Abstract: Antioxidative activities of carotenoprotein from Pacific white shrimp shells extracted by trypsin from albacore tuna spleen were investigated. Carotenoprotein exhibited increased DPPH, ABTS radical scavenging activities, ferric reducing antioxidant power (FRAP), metal chelating activity, hydrogen peroxide, and hydroxyl radical scavenging activities as concentration increased up to 5 mg/mL ( p  < .05). ABTS radical scavenging activity of carotenoprotein was stable over a wide pH range (2–11) and temperature up to 100°C for 180 min. It was also stable in a simulated gastrointestinal tract model system. Carotenoprotein was able to reduce lipid oxidation in a dose‐dependent manner. During storage at room temperature, light and dark, 4°C and −20°C for 12 weeks, the ABTS radical scavenging activity of carotenoprotein was stable with more than 75.75% activity retention. Therefore, Pacific white shrimp carotenoprotein may be used as an alternative source of natural antioxidants. Practical applications: Carotenoprotein from Pacific white shrimp shells, the by‐products from shrimp processing industry, can be extracted using tuna trypsin. This product possessed antioxidative activities and could serve as natural antioxidant to prevent lipid oxidation in foods.